2020
DOI: 10.1111/imcb.12363
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide promotes Drp1‐dependent mitochondrial fission and associated inflammatory responses in macrophages

Abstract: Mitochondria have a multitude of functions, including energy generation and cell signaling. Recent evidence suggests that mitochondrial dynamics (i.e. the balance between mitochondrial fission and fusion) also regulate immune functions. Here, we reveal that lipopolysaccharide (LPS) stimulation increases mitochondrial numbers in mouse bone marrow‐derived macrophages (BMMs) and human monocyte‐derived macrophages. In BMMs, this response requires Toll‐like receptor 4 (Tlr4) and the TLR adaptor protein myeloid diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 58 publications
6
53
2
Order By: Relevance
“…To investigate whether LPS-induced changes in mitochondrial morphology were due to DRP1 post-translational modification, we tested the effect of LPS stimulation on DRP1 phosphorylation at its activating site (Ser635) and inhibitory site (Ser656) during LPS stimulation. Similar to a recent report, we observed a trend in increased DRP1 Ser635 phosphorylation, yet no change in DRP1 Ser656 phosphorylation during 4 h LPS stimulation ( Figures S1B, C ) ( Kapetanovic et al., 2020 ). Furthermore, we examined the effect of LPS stimulation on expression of the key DRP1 adaptor protein Mitochondrial Fission Factor (MFF) as well as the well-characterized fusion regulators Mitofusin-2 (MFN2) and OPA1 ( Figures S1B, C ).…”
Section: Resultssupporting
confidence: 91%
“…To investigate whether LPS-induced changes in mitochondrial morphology were due to DRP1 post-translational modification, we tested the effect of LPS stimulation on DRP1 phosphorylation at its activating site (Ser635) and inhibitory site (Ser656) during LPS stimulation. Similar to a recent report, we observed a trend in increased DRP1 Ser635 phosphorylation, yet no change in DRP1 Ser656 phosphorylation during 4 h LPS stimulation ( Figures S1B, C ) ( Kapetanovic et al., 2020 ). Furthermore, we examined the effect of LPS stimulation on expression of the key DRP1 adaptor protein Mitochondrial Fission Factor (MFF) as well as the well-characterized fusion regulators Mitofusin-2 (MFN2) and OPA1 ( Figures S1B, C ).…”
Section: Resultssupporting
confidence: 91%
“…Macrophages play a pivotal role in modulating the hepatic immune microenvironment and inflammatory response in ALF [ 19 ]. As previous studies showed that LPS exposure usually induced mitochondrial dysfunction in macrophages [ 20 , 21 ], we further investigated the effect of selonsertib in protecting the mitochondrial function and dynamics of hepatic macrophages. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have proven that the danger of ALF is dependent on liver immune homeostasis and the inflammatory microenvironment, which is mainly modulated by macrophages [ 19 , 37 ]. As LPS exposure is known to induce macrophage mitochondrial dysfunction in acute tissue injury [ 21 ], we then investigated the effect of selonsertib in protecting the mitochondrial function and dynamics of hepatic macrophages and also used LPS-primed macrophages as an in vitro model to determine this issue. We found that selonsertib pretreatment effectively prevented LPS-induced activation of JNK and DRP1 and mitochondrial dysfunction in primary hepatic macrophages and macrophagic cell line and also suppressed the release of the proinflammatory cytokines TNF-α and IL-1α, which are known as major cytokines causing liver injury and inflammation [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies proved that the danger of ALF was dependent on the liver immune homeostasis and in ammation microenvironment mainly modulated by macrophages [17,35]. As LPS exposure was known to induce macrophage mitochondrial dysfunction in acute tissue injury [19], we then used LPS-primed macrophages as in vitro model to determine whether selonsertib could protect the mitochondrial function of macrophages in ALF. We found that selonsertib pretreatment effectively prevented the LPS-induced mitochondrial dysfunction of macrophage and the release of pro-in ammatory cytokines TNF-α and IL-1α, which were known as major cytokines causing liver injury and in ammation [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages play a pivotal role in modulating hepatic immune microenvironment and in ammatory response in ALF [17]. As previous studies showed that LPS exposure usually induced mitochondrial dysfunction in macrophages [18,19], we further determine the role of selonsertib in protecting mitochondrial function in the LPS-primed mouse macrophage cell line, RAW264.7. As we expected, LPS exposure induced a marked increase in the mitochondrial oxidative stress in macrophages as indicating by MitoSox, while selonsertib treatment signi cantly weakened the red uorescence intensity in the LPSprimed macrophages ( Figure 4A-left).…”
Section: Selonsertib Prevents Mitochondrial Damage Of Macrophages In mentioning
confidence: 95%